Infrastructure Challenges Caused by Industrial Transformation to Achieve Greenhouse Gas Neutrality. Ammonia Production in the Antwerp‐Rotterdam‐Rhine‐Ruhr Area. Issue 3 (21st December 2020) - Ausfelder, Florian; van de Beek, Floris; Bhardwaj, Rajat; Graf, Frank; Meinke‐Hubeny, Frank; Lodewijks, Pieter; Müller, Sabrina Alexandra; Rijkers, Monique; Perez Sanchez, Diana; Ruf, Johannes
Abstract: Several pathways for potentially greenhouse gas neutral production of ammonia have been investigated compared to today's conventional ammonia production at chemical sites in Antwerp, Dormagen, and Geleen. These pathways include on‐site water electrolysis using grid electricity, off‐site production via water electrolysis using renewable electricity and supply of green hydrogen to the site, pyrolysis of natural gas and conventional ammonia production coupled with CO2 ‐capture on‐site and transport to a storage site. All pathways effectively eliminate scope 1 emissions present in conventional production but continue to emit scope 2 emissions from grid electricity consumption. Eventually, a coordinated industry‐wide and cross‐industry effort is needed to address the transformational changes and develop the common cross‐border infrastructures. Abstract : Technology pathways for greenhouse gas (GHG) neutral production of ammonia are investigated and evaluated in terms of GHG reduction, specific production cost and competitiveness with respect to conventional production. These pathways pathway lead to specific infrastructure requirements, which are best addressed with a regional strategy.